Micronations and Postnational Rhetorics. Issue 4 (2nd October 2018) - Chirindo, Kundai
Abstract: This essay challenges the model of nationalism long favored in rhetorical scholarship by repositioning it as just one among numerous possibilities. To illustrate an alternative perspective, I employ a new materialist approach to postcolonial nations in sub-Saharan Africa. Specifically, I draw on Wangari Maathai's later work to juxtapose Westphalian nationalism to micronationalism. I argue that close attention to spatial and material dynamics in the African postcolonial context compels us to reconsider rhetoric's ties to the nation-state. I highlight some consequences of the materiality of space, nation, and rhetoric for rhetorical studies in thinking about rhetoric and (post)nationalism.